Minimizing the fuel consumption and the risk in maritime transportation: A bi-objective weather routing approach. (December 2017) - Veneti, Aphrodite; Makrygiorgos, Angelos; Konstantopoulos, Charalampos; Pantziou, Grammati; Vetsikas, Ioannis A.
Highlights: A time-dependent algorithm is presented for the ship weather routing problem. Given a maximum travel duration constraint, fuel consumption and risk are minimized. Improvements of the approach are proposed for faster execution but similar solutions. Techniques are also presented that improve the practicality of the derived solutions. Abstract: The paper presents an improved solution to the ship weather routing problem based on an exact time-dependent bi-objective shortest path algorithm. The two objectives of the problem are the minimization of the fuel consumption and the total risk of the ship route while taking into account the time-varying sea and weather conditions and an upper bound on the total passage time of the route. Safety is also considered by applying the guidelines of the International Maritime Organization (IMO). As a case study, the proposed algorithm is applied for finding ship routes in the area of the Aegean Sea, Greece. Enhancements of the proposed algorithm are also presented which improve the efficiency of our approach.